Lesson revisited: laparoscopic prowess in bowel endometriosis: a case report on management of endometriosis involving the sigmoid colon and appendix - Limbachiya, Dipak; Datta, Amrita; Agarwal, Manoj; Chandrakar, Saurabh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Endometriosis is a chronic inflammatory disorder affecting 10-12% of reproductive-age women. Although it primarily involves pelvic organs, bowel endometriosis accounts for approximately 10% of cases, predominantly affecting the rectosigmoid region. Symptoms may be nonspecific, and imaging findings can be misleading, often delaying diagnosis. Surgical intervention remains both diagnostic and therapeutic, with laparoscopy now favored for its precision and reduced morbidity. We present a case of a 26-year-old woman with acute lower abdominal pain radiating to the right shoulder, alongside a six-month history of dyschezia, dyspareunia, and vaginal dryness. Imaging suggested a left-sided endometriotic ovarian cyst adherent to the uterus with suspicion of sigmoid involvement. Laparoscopic exploration revealed endometriotic lesions involving the sigmoid colon, appendix, and left ovary. Surgical management included bilateral ureterolysis, left ovarian cystectomy, segmental sigmoid colectomy with nerve-sparing side-to-side anastomosis, and appendicectomy. Specimens were retrieved via colpotomy. The patient had an uneventful recovery and reported significant symptom improvement at follow-up. This case highlights the complex presentation of bowel endometriosis and the pivotal role of laparoscopy in diagnosis and management. Segmental colectomy with nerve-sparing techniques ensures complete resection while preserving autonomic function and optimizing outcomes. Appendectomy is advisable when appendiceal involvement is suspected. Vaginal specimen retrieval may further reduce postoperative morbidity. Multidisciplinary collaboration and patient-specific surgical planning are essential in managing extensive bowel endometriosis.